A cascaded converter for hybrid energy storage systems - Jie, Huamin (2019)
In recent years, due to the wide application of renewable energy, hybrid energy storage system (HESS) which is a combination of many types of energy storages (ESs) received an increasing attention. Each energy storage component has its characteristics and utility to meet the different needs of the load and external energy sources. Thus, properly matched with different ESs can improve the overall performance of the system. This final year project verifies a multiport tri-level (MPTL) converter with a two-stage structure for HESS which consists of a supercapacitor with high power density and two lead-acid batteries with high energy density. Because of its unique structure, the proposed converter has many advantages over the conventional converters, including reducing component size, improved extension capability, and controlling flexibility. On top of that, for external PV changes, HESS can respond quickly and adjust the charge and discharge process. Ultimately, the voltage of the load can maintain a stable value, which means that the actual operation of the load can be ensured, no matter how the external conditions changes. In this report, software experiments in Matlab Simulink and hardware experiments in dSPACE MicroLabBox will be carried out step by step, and the feasibility and effectiveness of the system will be verified through detailed analysis of the results.